Officiating speech association of Asia-Pacific Business Schools (AAPBS) academic conference / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
The AAPBS Academic Conference is a special event that gathers heads and deans of business schools from universities across the Asia-Pacific region. The Asia-Pacific region is undoubtedly one of the most economically vibrant regions in the world. 5. As heads and deans of business schools in this region, you have a unique opportunity and responsibility to shape the future of education and work. Your participation in this academic conference suggests that you are equally adamant about boosting graduate employability. The conference theme this year "Learned Values-Driven Talent: Towards Quality Education" highlights the importance of instilling values in our students. As we face unprecedented social, economic, and environmental challenges, it is essential that we equip our students with the autonomy, sense of purpose, and skills they need to succeed in the workforce and contribute to society.